Initiatives to broaden safety concerns in anaesthetic practice: The green operating room. Issue 1 (May 2021) - Beloeil, Helene; Albaladejo, Pierre
Abstract : The health sector is a major contributor to climate change through its large carbon footprint. Hospitals are highly energy and resource intensive. Operating rooms (ORs) contribute to a major part of these emissions because of anaesthetic gases, energy-intensive equipment and waste. Besides initiatives aimed to mitigate hospitals' climate footprints, health care professionals need to be involved in this process by changing their professional and personal behaviours without compromising the quality of care. Education on metrics (greenhouse gases), concepts (life cycle) and strategies to reduce the health care footprint would help professionals to commit themselves to the issue. The 5R's rule (reduce, reuse, recycle, rethink and research) used to promote an environmentally friendly way of life can be applied to the medical field and especially to the operating room and anaesthesia. When applied in the ORs, these strategies help question the use of disposable devices, attires and packaging, as well as our professional and personal behaviour. Greening the ORs requires the engagement of all professionals as well as other departments (pharmacy, hygiene) and management. Economic and social co-benefits are expected from this process.